The entrepreneurial capital of SMEs and business compliance in New Zealand : a study of the relationship : a thesis presented in partial fulfilment of the requirements for the degree of Master of Public Policy at Massey University, Albany, New Zealand - de Bruin-Judge, Robyn Leigh (Massey University, 2006)
Despite New Zealand receiving the number one ranking for ease of doing business in a major international comparative survey of compliance requirements, SME owners continue to rate compliance as a significant concern. This research project set out to investigate why this was so. The qualitative research undertaken for this thesis involved case study interviews with six SME owners. A resource-based approach was taken, looking at the resources SME owners needed to address the compliance task, and how they sourced and applied these. The scope of the study extended beyond the confines of the workplace to encompass the impact of compliance on the personal lives of SME owners and their families. Firkin’s model of entrepreneurial capital was applied and extended. Accordingly, the study encompassed an examination of economic, human, social, cultural and personal capital. An original concept, temporal capital, was developed to address the application of ‘potentially productive time’ as a resource. The findings are applied to a discussion of the Quality Regulation Review currently underway in New Zealand. It is recommended that SME issues could be more comprehensively addressed by incorporating screens within the Business Cost Calculator that estimate the relative psychic and opportunity costs associated with proposed regulations. A gender analysis of the compliance task was also undertaken. This revealed that the impact of compliance measures may be disproportionately borne by those whose business and personal lives are intertwined, primarily women. The invisibility of these workers has contributed to their needs being inadequately addressed by traditional processes of consultation and data analysis. The thesis concludes that it is not the regulatory regime alone that determines ease of doing business. It is the match between the requirements of the regime and the compliance-related entrepreneurial capital accessible to those subject to it. Recommendations relate therefore, to improving both the institutional capital of the regulator and the compliance-related entrepreneurial capital accessible to the SME.
Keywords: Small business; Business cost calculator; Compliance; New Zealand; Social capital; Cultural capital; Gender analysis; Fields of Research::360000 Policy and Political Science::360200 Policy and Administration::360201 Public policy